Changes in the prevalence of atrial fibrillation in the Russian population over a 13-year follow-up - M. Yu. Shapkina; E. V. Mazdorova; E. M. Avdeeva; L. V. Shcherbakova; A. N. Ryabikov; J. A. Hubachek; M. Bobak; S. K. Malyutina (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To study the prevalence of atrial fibrillation (AF) in the Russian urban population cohort aged 45-69 years and its changes over 13-year follow-up during aging.Material and methods. This cross-sectional long-term prospective study included random population sample of men and women 45-69 years (n=9360, HAPIEE project, Novosibirsk), which was examined in 2003-2005 and was re-examined twice and followed up for about 13±1,00 years in men and 13,1±2,17 years in women. The incidence of AF was assessed for individuals without AF or cardiovascular disease (CVD) at the baseline examination. Statistical analysis was performed using the SPSS software package (v.13.0).Results. In a population sample over a 13-year follow-up, AF prevalence increased from 1,6% (1,1% among women and 2,1% among men) at the age of 45-69 years to 4,2% (3,0% among women and 6,1% among men) aged 55-84 years according to screening rest ECG examinations. The prevalence of new AF cases over a 13-year followup in the cohort of 45-69 years old without previous CVD and AF was 5,6%, of which 40% were paroxysmal. The mean age at the time of first registered AF was 69±6,93 years, and was 2 years higher in women (70,0±6,83) than in men (68±6,93). The average period before the AF onset among people aged 45-69 years without baseline CVD and AF was 7,5±3,83 years for men and 8,1±4,02 years for women. The total prevalence of AF in the population sample was 8,3%. The highest AF prevalence was registered at the age of 65-69 years (11,4%) for men and 5 years later for women (12,0%) (p80 years decreased and amounted to 4,1% among men and 5,7% among women.Conclusion. In the Russian population sample (Novosibirsk) aged 45-69, the AF prevalence increased from 1,6 to 8,3% over 13 years of follow-up. In addition, 473 new AF cases were identified, ~40% of which were paroxysmal AF. The prevalence of AF in the Siberian population sample for the 45-60 years age group is comparable with the large Russian and North American studies, but higher for persons aged 60-74 years and lower for older age group, for both men and women.